A new species of Anobothrus (Polychaeta, Ampharetidae) from the Weddell Sea (Antarctica), with notes on habitat characteristics and an updated key to the genus - Säring, Friederike; Bick, Andreas; Link, Heike (European Journal of Taxonomy, 2022)
Benthic samples were collected during two expeditions near the Antarctic Peninsula and in the South-Eastern Weddell Sea. During these studies, a new species of Ampharetidae Malmgren, 1867, Anobothrus konstantini Säring & Bick sp. nov., was found. Here we present a detailed description of this species. We used the traditional light microscope and scanning electron microscope (SEM) to identify and describe the diagnostic characters: a circular glandular band on segment 6; an elongate ridge between the notopodia on segment 12 and modified notochaetae on this segment; 16 thoracic, two intermediate and ten abdominal segments. For the first time, micro-computed tomography (micro-CT) was used for a species description of Anobothrus. Micro-CT provided information on the shape of the prostomium (Ampharete-type) and the arrangement of branchiae (four pairs in two rows, without a gap). In addition, we provide quantitative information on the environmental niche based on sediment parameters (chlorophyll a content, organic matter content, chloroplast equivalent, grain size) for the new Anobothrus species, relevant for, e.g., species distribution modelling. Finally, an identification key for all Anobothrus species is provided.